AN EMPIRICAL LEGAL STUDY ON AGRICULTURAL TRIBAL LABOUR IN INDIA - .Ch, Dr.Anil Babu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Agriculture is one of the three most hazardous sectors of activity, both in industrialized and developing countries. According to estimates from the International Labour Office (ILO), some 170,000 agricultural workers are killed each year. This means that workers in agriculture run at least twice the risk of dying on the job as compared with workers in other sectors. Agricultural mortality rates have remained consistently high in the last decade as compared with other sectors, where fatal accident rates have decreased. Millions of agricultural workers are seriously injured in workplace accidents with agricultural machinery or poisoned by pesticides and other agrochemicals. Agricultural workers constitute the most neglected class in Indian rural structure. Their income is low and employment irregular. Since, they possess no skill or training, they have no alternative employment opportunities either. Socially, a large number of agricultural workers belong to scheduled castes and scheduled tribes. Therefore, they are a suppressed class. They are not organized and they cannot fight for their rights. Because of all these reasons their economic lot has failed to improve even after four decades of planning.